Analisis Kinerja Keuangan Sebelum dan Sesudah Right Issue - Rini Anisa; Acep Samsudin; Dicky Jhoansyah (Journal of Management and Bussines (JOMB), 2019)
This Research was meant to analyze the differences in the company's financial performance before and after the rights issue for companies on the IDX for the period 2015-2016. The financial performance measurement method uses the analysis of the wicoxon signed rank test which uses several financial ratios from several components. In the income statement and balance sheet, namely Current Ratio (CR), Debt to equity ratio (DER), Total asset turnover (TATO), Return on equity (ROE). Sampling in this study using purposive sampling method, the sample in this study amounted to 15 companies on the IDX that carried out rights issues for the period 2015-2016. The results of this study indicate that there are significant differences in the ratio of CR, DER and TATO two years before and two years after the rights issue, while in the ROE ratio there are no significant differences two years before and two years after the rights issue. This result shows that the company's financial performance two years before and two years after the rights issue is more efficient in increasing short-term and long-term debt and in utilizing the company's sales assets to increase. Keywords: Right Issue, Current Ratio, Work Analysis